Genetic diversity and antimicrobial resistance of clinical Klebsiella pneumoniae isolates: An ISSR-PCR analysis - Poonamrani Mishra; Debasish Sahoo; Mahesh Chandra Sahu (Journal of Infection and Public Health)
Background: Klebsiella pneumoniae is a major nosocomial pathogen associated with severe infections and increasing antimicrobial resistance. The study aimed to investigate the genetic diversity of K. pneumoniae clinical isolates using Inter Simple Sequence Repeat (ISSR) primers to assess strain differentiation and evolutionary relationships. Methods: A total of 144 K. pneumoniae isolates were obtained from clinical samples in a tertiary care hospital. Standard microbiological and biochemical techniques were used for bacterial identification. Antibiotic susceptibility testing was performed using the Kirby-Bauer disk diffusion method. Genomic DNA was extracted, and ISSR-PCR was conducted using 19 primers to analyze genetic diversity. Banding patterns were scored, and genetic relationships were determined using Jaccard's coefficient and the Unweighted Pair Group Method with Arithmetic Mean (UPGMA) to construct a phylogenetic dendrogram. Principal Component Analysis (PCA) was also applied to assess variability among isolates. Results: The antibiotic resistance profile revealed a high prevalence of multidrug-resistant (MDR) K. pneumoniae, with resistance to beta-lactams, aminoglycosides, and fluoroquinolones. ISSR-PCR analysis exhibited significant genetic polymorphism, with ISSR 1, ISSR 7, and ISSR 15 generating the highest number of bands. The resolving power of ISSR 11 and ISSR 14 was the highest (0.889 and 0.867), indicating their efficacy in distinguishing closely related strains. Phylogenetic analysis clustered the isolates into two major groups, suggesting genetic heterogeneity. PCA further confirmed genetic variability, with distinct clusters forming among isolates. Conclusion: The study underscores the genetic diversity of K. pneumoniae isolates and the utility of ISSR markers in bacterial typing. The high prevalence of MDR strains highlights the urgent need for enhanced molecular surveillance and infection control strategies. ISSR-PCR offers a cost-effective alternative for epidemiological studies, though integration with whole-genome sequencing could provide deeper insights into resistance mechanisms.